Historic territory in the context of countryside transformation. The experience of the old, traditional, rural landscape in the Wielkopolska Region, Poland - Markuszewska, Iwona (Scienze del Territorio, 2017)
Old agricultural landscapes are valuable, mostly due to cultural values: the history of the place and its tradition. However, in these kinds of landscape, not only the cultural aspects that are important, but also the natural elements which are essential in the holistic assessment of landscape. For this reason, both the cultural heritage and the natural beauty of landscape should be taken into consideration when it comes to the issue of the protection of traditional agrarian landscapes, especially in rural areas located in the close vicinity of cities and towns. This paper presents the results of a preliminary study on changes in an old, traditional, rural landscape as a consequence of urban sprawl and development of non-farming purposes. As a study case, the environs of NowyTomyśl, the area of a Dutch settlement in the Wielkopolska Region (Poland) was chosen. In this region the remnants of a unique landscape pattern, rural settlement and rural architecture design can still be found despite the ongoing intensive process of landscape alteration.